2014
DOI: 10.1155/2014/623487
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Disease Duration in Alzheimer’s Disease: A Postmortem Study of 103 Cases Using the Kaplan-Meier Estimator and Cox Regression

Abstract: Factors associated with duration of dementia in a consecutive series of 103 Alzheimer's disease (AD) cases were studied using the Kaplan-Meier estimator and Cox regression analysis (proportional hazard model). Mean disease duration was 7.1 years (range: 6 weeks–30 years, standard deviation = 5.18); 25% of cases died within four years, 50% within 6.9 years, and 75% within 10 years. Familial AD cases (FAD) had a longer duration than sporadic cases (SAD), especially cases linked to presenilin (PSEN) genes. No sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 51 publications
2
22
1
Order By: Relevance
“…Mean survival of the 84 FTLD-TDP cases was 7.9 years, similar to the 7.1 years recorded in a recent study of 102 AD cases [5], but longer than the 5.2 years and 6.5 years in AD estimated by Doody et al [26] and Feldman et al [27] respectively. Mean survival was also greater than the 6.08 years reported for a large sample of pre-senile dementia cases in the north of England, UK, but which comprised largely AD and vascular dementia (VD) [36].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Mean survival of the 84 FTLD-TDP cases was 7.9 years, similar to the 7.1 years recorded in a recent study of 102 AD cases [5], but longer than the 5.2 years and 6.5 years in AD estimated by Doody et al [26] and Feldman et al [27] respectively. Mean survival was also greater than the 6.08 years reported for a large sample of pre-senile dementia cases in the north of England, UK, but which comprised largely AD and vascular dementia (VD) [36].…”
Section: Discussionsupporting
confidence: 82%
“…In addition, the data suggested that survival was similar in familial and sporadic FTLD-TDP. This result contrasts with AD in which familial cases in general and cases specifically linked to presenilin 1 (PSEN1) mutation exhibited increased survival [5].…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations